Peran Supervisi Kepala Sekolah dalam Meningkatkan Kinerja Guru PAI Di SMP Negeri 1 Marisa - Darmawati Darmawati; Muliani Muliani (Education and Learning Journal, 2023)
This research is included in the type of qualitative descriptive research because it describes the facts or a picture of leadership on the performance of PAI teachers. The subjects of the research were the principals and PAI teachers. Data collection techniques through interviews. The results of the research conducted illustrate that if the teacher experiences obstacles in the teaching and learning process, the teacher will find his own solution or if it is deemed necessary to communicate with other teachers it will be carried out by the teacher, both in one school and in MGMP. Supervision of school principals in improving the performance of PAI teachers has been very good, but in this case, the principal's leadership must continue to be developed so that the performance of PAI teachers is increasing and the output to students is better. The principal as a policy maker must be able to move the wheels of the organization optimally. Building the quality of PAI teachers who have reliable competencies is not enough to build in a short time, but must be built in a comprehensive and sustainable manner, superior resources are not born just like that but there must be someone who is able to drive and make breakthroughs through a policy and this is only leaders and stakeholders who are expected to be able to make the breakthrough. The principal's supervision of the performance of PAI teachers will only lead to success because from the research conducted the output produced is still not optimal. This supervision must be improved so that in the future PAI teachers and other teachers are more disciplined in preparing teaching materials and are active and professional in providing learning.